Analysis of influence and composition of the metal alloys of two implant drill system - Lara Rabelo Aragão; Jiovanne Rabelo Neri; Pedro Henrique Gonçalves Holanda Amorim; Rafael Linard Avelar; Isabelle Ramos Pereira Lima; Roque Soares Martins; Alex Oliveira De Moura; Thiago Vasconcelos Melo (Global Journal of Medical Research, 2023)
Purpose The mechanical behavior of two different implant drill systems for osteotomy preparation using polyurethane foam models were evaluated Methods Fourteen polyurethane foam models and 28 Neode nt drills and 28 Dentoflex drills were used In a controlled environment the perforations were timed and an infrared digital thermometer and a K-type sensor were used to measure the temperature before and after perforations Each group was divided into 7 subgroups S5 5 perforations S10 10 perforations S15 15 perforations S20 20 perforations S30 30 perforations S40 40 perforations and S50 50 perforations Results In the S5 and S10 subgroup drilling time of the drills with three helical cutting edges was longer p 0 05 and temperature 1 was lower p 0 034 in the S10 group